A comprehensive review of stroke-related signaling pathways and treatment in western medicine and traditional Chinese medicine - Chen, Binhao; Jin, Weifeng (Frontiers in Neuroscience, 2023)
This review offers a analysis of stroke pathophysiology, highlighting its intricate network nature involving multiple signaling pathways and mechanisms. The historical progression and research advances in stroke-related signaling pathways, emphasize the potential crosstalk among them and underscoring the fact that stroke is a complex network disease. The interplay between the Hippo signaling pathway and the ferroptosis pathway is explored, revealing their potential relevance to stroke. Stroke is a complex network disease, as seen from its pathophysiological mechanism and the extensive role of its signaling pathways. The involvement of multiple signaling pathways such as SHH, Nrf2/ARE, HIF-1α, PI3K/AKT, JAK/STAT, AMPK in oxidative stress and ferroptosis further underscores this complexity. The PI3K/AKT signaling pathway, for instance, is implicated in various processes including angiogenesis, inflammation, autophagy, and apoptosis. However, there remain several intricate and unexplored crosstalk pathways such as ferroptosis and the interaction between the Hippo and Wnt signaling pathway. The study elaborates on key TCM therapies, such as Rehmannia and Astragalus. As stroke is a network disease, TCM has the potential and advantages of treating stroke with multi-target and multi-pathway mechanism of action. Overall, the passage offers insights into stroke pathophysiology and treatment, emphasizing the importance of considering the complex network nature of stroke-related signaling pathways and mechanisms.